Immunotherapy targeting liver cancer tumor-initiating cells: challenges, mechanisms, and emerging therapeutic horizons - Yinying Chai; Tinghui Xu; Xin Chen; Bihua Chen; Xinghai Du; Zhezhong Zhang (Frontiers in Immunology)
Liver cancer is a major global health burden, with hepatocellular carcinoma (HCC) being the most common type. Liver cancer tumor-initiating cells (TICs) are responsible for recurrence, metastasis, and therapeutic resistance, thereby presenting formidable treatment challenges. This review provides a comprehensive summary of the biological features of liver cancer TICs, including their potential cellular origins, diagnostic difficulties, key signaling pathways, and complex interactions with the tumor immune microenvironment. Special emphasis is placed on immunotherapeutic strategies, which have shown notable progress but remain limited by TIC-induced immune resistance. The review discusses current approaches such as immune checkpoint inhibitors (ICIs), adoptive cell therapies, and tumor vaccines, as well as combination strategies integrating immunotherapy with chemotherapy, targeted therapy, and locoregional interventions. Furthermore, emerging strategies including gene editing, targeted tyrosine kinase inhibition, and artificial intelligence-based tumor prediction are being explored for their potential to improve therapeutic efficacy. The significance of this review lies in highlighting the importance of surmounting the challenges presented by TICs to boost the efficacy of liver cancer treatment. In conclusion, although existing treatment approaches have demonstrated promise, further research is warranted to elucidate the origins of TICs, establish accurate diagnostic methods, and overcome resistance, ultimately enhancing the efficacy of liver cancer treatment and improving patient outcomes.